Health surveillance in Brazil: the challenges of the sanitary risks in the xxi century and the necessity of a national health surveillance system - Aith, Fernando; Dallari, Sueli Gandolfi (Journal of Health Law, 2009)
The technological development experienced in the contemporary world are transforming society and relations between State and people. The mobility of human being has reached levels never before imagined and a person can move from one side of the world to the other side in less than 24 hours. This mobility also includes goods and services, giving the keynote of the globalized world of the XXI Century. In this context, the risks of diseases and others health problems are intensely amplified. Nowadays, an epidemic that begins in China can arrive in Brazil the following day. Brazil recognizes health as a universal right and also consider it a State's obligation. Therefore, the State of Brazil is obligated to organize itself to eliminate or control health risks. Today, the organization of the Brazilian State regarding the surveillance of risks of diseases and other health problems is fragmented and includes sanitary surveillance (focused on goods, products and services), epidemiological surveillance (diseases and investigations of other risks) and environmental surveillance in health (the environment in general, including the workplace). This fragmentation causes problems for the management and consolidation of strategic information for health protection. Brazil has the need to think about an other model of organization that put together all "kinds" of surveillances within a single coordinated system, called the National System of Health Surveillance, which would be able to coordinate the various specialties of health surveillance that exists in the country in order to provide a effective system of information and health surveillance, able to face emergency situations of public health.